Tingkat Kepuasan Siswa dalam Pelayanan Arah Peminatan pada Implementasi Kurikulum 2013 - Qolbina, Yanuar Fitroh (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
The purpose of this study is to determine how much the level of students’ satisfaction in service towards specialization in the implementation of Curriculum 2013 and determine the service procedure towards specialization in the implementation of Curriculum 2013. The populations in this study were 11th grade students of SMA Negeri 1 Muntilan, amounting to 250 students and a sample of 129 students were taken by using simple random sampling. Methods of data collecting used were psychological scale and interviews. Data were analyzed using descriptive analysis techniques. The results showed the level of student satisfaction was the criterion quite satisfied with the score as much as 62%. In addition, placement process ofspecialization class did not cover the aspects towards specialization which should be the basis for the consideration of the direction of specialization. This indicated that the level of students’ satisfaction was not maximal yet, seen from the figure of 62% which meant that it only belonged to quite satisfied category. And it was still going on inaccuracies in the procedures of service implementation towards specialization.